How do they deal with the Pandemic? The effect of secure attachment and mindfulness on adolescent resilience - Aini, Dewi Khurun; Sessiani, Lucky Ade; Darmuin, Darmuin; Stück, Marcus (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Building resilience in adolescents is an important need, especially for those who spend most of their time at home with their families while facing the pandemic situation. Resilience enables adolescents to survive, adapt, and rise up when faced with difficult circumstances. This study aims to empirically examine the role of secure attachment and mindfulness in adolescent resilience in the new normal era. The study subjects were 220 junior high school students in Semarang City, Indonesia, who were selected using the convenience sampling technique. The study is based on correlational quantitative research using regression analysis. The instruments used were the Secure Attachment Scale, Mindfulness Scale, and Resilience Scale. The results show that there was a significant and positive relationship between secure attachment and mindfulness, and adolescent resilience in the new normal era (R2 = .56, F = 16169, p < .01). The findings provide useful suggestions for families to emphasize the development of psychological skills, especially resilience in adolescents, throughout the country.